Pretreatment to increase yield and antioxidant activity of _-oryzanol in rice bran oil - Duangkamol Ruen-Ngam; Chitti Thawai; Sujitra Sukonthamut (My University, 2016)
Six pretreatment processes to extract oil from Khao Dok Mali 105 rice bran were tested to assess the effect of the processes on the γ-oryzanol content and DPPH scavenging activity of the extract.The pretreatment processes consisted of the following: microwave heating (60-110 °C), hot air heating (70-180 °C), roasting (60-80 °C), parboiling (70 °C), autoclaving (121 °C), and enzyme (amylase) treatment (50 °C).The highest amount of oil was obtained by hot air heating (70 °C) of 0.27 g/g of dried rice bran, whereas the highest γ-oryzanol yield was obtained by parboiling 9.8 mg/g of dried rice bran.The highest γ-oryzanol concentration obtained with a roasting pretreatment (60 °C) was 46.9 mg/ml of rice bran oil.
Keywords: Rice bran oil; Edible Oils Quality and Analysis